Intentional Homicides and Alcohol Abuse in Lithuania - Černevičiūtė, Sigita (Journal of contemporary criminal justice, 2024)
The aim of the present study is to examine the links between high intentional homicide rates and alcohol abuse in the context of social transition in Lithuania. According to the extant literature, both the increase in homicide rates and the increase in alcohol abuse have a negative impact on public health and are often associated with challenges at the macrosocial level. In recent decades, Lithuania has experienced substantial political, economic, and social transformations. Lithuanian society has transitioned from a Soviet regime to embrace the Western principles of liberal democracy. Yet, despite positive political and economic progress, Lithuania remains a country with one of the highest homicide and alcohol-related harm rates in the European Union. These characteristics have made the Lithuanian homicide situation a captivating topic for a range of international and national studies, expert analyses, and evaluations. Unfortunately, the lack of reliable and consistent data on homicide continues to obstruct researchers from delving deeper into the analysis and explanation of the homicide phenomenon in Lithuania. To mitigate this issue, in this work, we present thoroughly collected and processed historical data on intentional homicide trends from 1961 to 2022. We also examine changes in the rate of homicide suspects, including their socio-demographic characteristics and alcohol intoxication for the 2004–2022 period. Finally, we investigate changes in homicide mortality rates and homicide victims’ socio-demographic characteristics. Our analyses are based on data sourced from the Lithuanian Special Archives, as well as national and international databases of crime statistics and demographic data. We noted a continuous decline in intentional homicide rates after the steep increase in 1989–1994. Furthermore, between 2004 and 2022, more than half of intentional homicide suspects were under the influence of alcohol. These findings are discussed in the broader context of societal changes in Lithuania.